JUAL BELI EMAS SECARA TIDAK TUNAI DITINJAU SECARA HUKUM FIKIH - Midisen, Kisanda; Handayani, Santi (Jurnal Ekonomi Syariah Pelita Bangsa, 2021)
Today's gold is only valued as women's jewelry. As an investment platform. Rotting, buying and selling gold too. Increasingly. easy, on reality buy gold already. The growth from cash to non-cash markets is due to the high interest in investment in gold with the exchange of goods as cash as it is, it raises questions. That have developed in communities of clean and illegitimate laws. This research is a type of library literature research. In research researchers use the normative and textual approach, that is, to examine the problem in an existing framework of values based on texts and Islamic law, government regulation and other texts relating to dalarm discussion. In the study it may be concluded that the unlawful sale of gold was two opinions: the first opinion was haram, it was the view of clerical mayonnaise (mahzhab Hanafi, Maliki, Syafi’i and Hambali) and the second opinion was the mubah, this is the opinion of Ibn Taimiyah and Ibn Qayim, as well as contemporary scholars who agree.